Alanine aminotransferase elevation in obese infants and children: a marker of early onset non alcoholic fatty liver disease - Engelmann, Guido; Hoffmann, Georg F.; Grulich-Henn, Jürgen; Teufel-Schäfer, Ulrike (Hepatitis monthly, 2014)
Elevated aminotransferases serve as surrogate markers of non-alcoholic fatty liver disease, a feature commonly associated with the metabolic syndrome. Studi ...